Organizational Maturity Assessment Model for Collaborative Networks - Schardosin F.Z.* (2021)
© 2021, IFIP International Federation for Information Processing.This paper aims to propose an organizational maturity assessment model for taking part in collaborative networks, aiming to contribute to the theory on this topic. It uses the mixed research method, with a qualitative approach, using systematic research and focus group techniques, to highlight the theoretical gaps and the establishment of evaluation criteria, and a quantitative approach with the use of the multicriteria decision-making method, to assign the importance of each criterion and establish the level of maturity of an organization. The result was an assessment instrument composed of eight dimensions and fifty-five categories, with the organization’s positioning in indicators according to the four possible levels for each category.